Kesesuaian Muatan Pelajaran Bahasa Indonesia Kelas IV Tema Indahnya Kebersamaan SD/MI - Putri Deapalupi, Aisyah; Susanto, Eri (Al-Azkiya: Jurnal Pendidikan MI/SD, 2021)
This study aims to analyze the content of Indonesian in terms of the use of sound and correct language and the suitability of image illustrations with the material in Theme 1 Beautiful Togetherness. This research uses a descriptive qualitative approach. The type of study chosen is in library research, which means that the researcher analyzes the teacher's book and student's book Theme 1, The Beauty of Togetherness. The method of quoting the data used is Forum Group Discussion (FGD). The result is Indonesian language learning material in Theme 1, The Beauty of Togetherness. It follows the EYD, and the illustrations used are apparent; however, some need correction not to misinterpret when the learning takes place